PENGEMBANGAN GOOGLE SITES UNTUK WEB PEMBELAJARAN DI SMKN 3 GARUT - Mustofa Husni Sanoval; Iman Nasrulloh; Aceng Ahmad Rodian Susila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of information technology opens opportunities to enhance learning quality through web-based media. This study aims to develop Google Sites-based learning media at SMKN 3 Garut using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research stages include needs analysis, design, development, implementation, and evaluation of the learning media. The results show that the developed Google Sites-based learning media achieved a very high feasibility level. Evaluation by media experts scored 94% in the "very feasible" category. Additionally, student trials indicated a very high acceptance rate with a score of 92%. This learning media effectively improves material accessibility, supports independent learning, and facilitates interaction between teachers and students. This study significantly contributes to the development of technology-based learning media, particularly in vocational high schools. The Google Sites-based media developed is expected to serve as a reference for web-based learning innovations to support teaching and learning processes in the digital era.